Deflection, torsion and edging measurement in alpine skiing - Spitzenpfeil, P.; Hummel, C.; Huber, A.; Waibel, K.; Menhorn, F.; Senf, B. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The deflection of the ski is crucial in alpine skiing, at least to achieve carved turns. In theory, due to the geometric shape of the ski, the ski deflects dependent on the achieved edge angle, supported by additional movements (Lieu et al. 1985). However, up to now, the proof of this (simplified) theory and the scientific validation in field measurements is missing (Thorwartl et al. 2022). In this study, a new measurement system is used to measure deflection of the ski in combination with torsion and edging.